Scientific Societies: Conversations on Change - Adrian, Judith; Sullivan, Sue L.; Stuckey, Richard E.; Schwecke, Warren M.; Massengale, Martin A.; Harriott, Bill L.; Godfrey, Daniel; Fischer, James R.; Cline, Molly N.; Castenson, Roger R.; Buse, Rueben C.; Bosserman, Steve; et al. (Council for Agricultural Science and Technology (CAST), 1996)
Summary of a workshop designed to create awareness of critical changes in the workplace. Members of nearly 50 professional societies participated.